Behavior generation for interactive virtual humans using context‐dependent interaction meshes and automated constraint extraction. (29th April 2015) - Vogt, David; Lorenz, Ben; Grehl, Steve; Jung, Bernhard
Abstract: Interaction meshes are a promising approach for generating natural behaviors of virtual characters during ongoing user interactions. In this paper, we propose several extensions to the interaction mesh approach based on statistical analyses of the underlying example interactions. By applying principal component analysis and correlation analysis in addition to joint distance calculations, both the interaction mesh topology and the constraints used for mesh optimization can be generated in an automated fashion that accounts for the spatial and temporal contexts of the interaction. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, we propose several extensions to the interaction mesh approach based on statistical analyses of the underlying example interactions. By applying PCA and correlation analysis in addition to joint distance calculations, both the interaction mesh topology and the constraints used for mesh optimization can be generated in an automated fashion that accounts for the spatial and temporal contexts of the interaction.